(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This article devoted to focus on the importance of phraseological units, phraseological features, and phenomenon. In this article, one can find information about the role of phraseology in the process of learning languages, the several types of phraseology which are essential in learning, period and advantages of phraseology in foreign language learning.